PARTICIPATION IN E-GOVERNMENT SERVICES AND SMART CITY PROGRAMS: A CASE STUDY OF MALAYSIAN LOCAL AUTHORITY - Lim, Seng Boon; Abdul Malek, Jalaluddin; Hussain, Mohd Yusof; Tahir, Zurinah (PLANNING MALAYSIA, 2020)
Public participation is gaining popularity in local governance practices where the involvement of the public in the decision-making process is essential in promoting good governance concepts. However, local authorities are facing challenges in guiding public involvement in e-government services such as smart city programmes. Hence, this paper aimed to examine the participation process in e-government services and smart city programmes, and later to recommend a framework to assess participation level and process in local context. Petaling Jaya, Malaysia, was selected as a case study where interviews and observations were conducted with thematic analysis based on relevant themes. Through the selected attributes and designated questions in the participation framework, time and effort can be saved in addition to clearing the ambiguities of stakeholders who are keen on gaining the authentic participation culture in e-services and smart city programmes. This study has provided new insights on how e-government can be implemented by the local government after adopting a smart city policy in the context of public participation.